Role of Expectations and Emotions in Pre-service Teacher Identity Construction - Shankar, Padmini (Journal of NELTA, 2023)
The construct of Language Teacher Identity has garnered tremendous research interest over the past two decades with teacher aff ect – the relationship between emotional factors and teacher identity construction – as one of the areas of focus. Pre-service teachers (PSTs) enter the teacher education program (TEP) with expectations of becoming ‘good’ teachers. These are negotiated and mediated through the practicum experience that entails enormous emotional investment on the part of the PSTs as they experiment with their developing skills and knowledge to transact learning. This paper explores the role of expectations and emotions in the emerging identities of PSTs. It examines: a) PSTs’ beliefs about ‘good’ teachers which translate into expectations, b) teaching events involving pleasant and unpleasant emotions for PSTs infl uencing the construction of a positive and negative sense of identity as teachers and c) ways in which PSTs negotiate and adjust their emerging identities as language teachers vis-à-vis their expectations and emotions. Five PSTs enrolled in a TEP at a Central University in India are the participants of the study. Reflective journals, classroom observation, and oral narratives are used as tools to collect data which is analyzed qualitatively. The fi ndings reveal that PSTs use several coping strategies to combat unpleasant emotions that erode their fragile emerging identities while exercising agency all through to develop positive identities with the help of pleasant emotions.